Polymerization of pyrrole and thiophene on polyethylene adipate electrodes - Erturan, S; Yalvac, B; Toraman, S (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 1998)
Polymerizations of pyrrole and thiophene on a platinum foil coated by polyethylene adipate (PEA) were carried out in acetonitrile by electrochemical methods. Different compositions of semi-conducting composite films of PEA/Polypyrrole(PPy), PEA/Polythiophene(PT) were prepared by the electrochemical polymerization of pyrrole and thiophene on PEA electrode. The polymerization was possible only for a certain thickness of the polyethylene adipate(PEA) on the platinum. Conductivities of PEA/PPy, PEA/PT, films at different compositions were obtained. The films were examined by FTIR spectroscopy. The topography of surface films were analyzed by a scanning electron microscope(SEM). The conductivity behaviour of (PEA/PPy), (PEA/PT) films at different compositions when exposed to Ar, Na, C3H8 and H-2 gases indicated that these films cannot be used as gas sensors.
Keywords: polyethylene adipate, polyethylene adipate; polypyrrole composite, polyethylene adipate; polypyrrole composite; ELECTROCHEMICAL POLYMERIZATION; CONDUCTING POLYPYRROLE; PLATINUM-ELECTRODES; POLYTHIOPHENE FILMS; COMPOSITES; Chemistry; Engineering